The Effect Of Work Discipline And Work Motivation On Employee Performance In The Cooperative Café Timor (CCT) Company in Ermera District. - Maria Mendonca Nunes; Hermien Tridayanti (Journal of World Conference (JWC), 2020)
This research was conducted at the Cooperative Café Timor Company (CCT) in Ermera District. This study aims to determine the Effect of Work Discipline and Work Motivation on Employee Performance. In this study using a tool in the form of observations, interviews and questionnaires to 31 respondents with data from this study using the population (census). In this study using the Likert scale method and this research is quantitative data. Data analysis techniques are, Test Validity, Reliability Test and normality test with alpha cronbach. Classical Assumption Test, Multicolonity Test, heteroscedasticity test, multiple linear analysis, hypothesis testing, t test, f test. Data collected was tested for validity and reliability with coefficient alpha (cronbach alpha). The results of this study as a whole show that Work Discipline partially has no effect on work motivation and employee performance. Because there is a system that is not good, and also the HR system obtained by the company is still ineffective.